Analisis Fikih Muamalah terhadap Akad Kerjasama Sponsorship Perusahaan Rokok dalam Kegiatan Keagamaan : Muamalah Fiqh Analysis of Cigarette Company Sponsorship Cooperation Agreements in Religious Activities - Andi Dahmayanti; Risdayani, Risdayani; Munawara, Munawara; Hayyul Maryam (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2025)
This research examines the sponsorship contract of cigarette companies in religious activities according to fiqh muamalah in line with the rise of this phenomenon in Indonesian Muslim society. This research aims to find out and understand the muamalah fiqh on sponsorship contracts related to the law of cooperation with cigarette companies in religious activities. This research uses descriptive qualitative research, which takes data sources from library books (library research) using a normative approach that uses the Qur'an and sunnah as the main reference and a sociological approach analysing interrelated social structures. The results showed that cigarette companies as sponsors in the religious field, which is seen as a condition inversely proportional to religious goals. Religion teaches us about taking care of ourselves, not doing damage on earth and not oppressing others. So that by sponsoring religious activities, it seems to support the spread of smoking itself, which we already know has a negative impact on the health of the body. The original law of the contract is valid, what is being discussed is the halalness of the object of the goods being promoted. This contract is not valid considering the harm and the law of this cigarette. This research is expected to contribute and become one of the sources of knowledge for knowledge seekers in knowing the law of sponsorship cooperation contracts in cigarette companies.